Risk Factors for Spontaneous Abortion - C Abeysena; P Jayawardana; R De A Seneviratne (College of Community Physicians of Sri Lanka, 2011)
Objective: To determine the risk factors for spontaneous abortion. Study design: A prospective cohort study was carried out in Sri Lanka from May 2001 to April 2002 to determine the risk factors for spontaneous abortion. Eight hundred and twenty pregnant mothers were recruited on or before 16 weeks of gestation and followed up until delivery. Socio-demographic, occupational exposures, psychosocial stress and physical activity in terms of posture during pregnancy were assessed. Logistic regression analysis was applied and results were expressed as odds ratios (OR) and 95% confidence intervals (95%CI). Results: Maternal age of > 35 years was a risk factor [OR 2.98; 95%CI: 1.07, 8.26] and walking > 2.5 hours/day was a protective factor [OR 0.31; 95%CI: 0.11, 0.92] for second trimester spontaneous abortions after controlling for confounding factors. Occupational exposures, psychosocial stress, alcohol consumption or exposure to passive cigarette smoke during pregnancy were not observed to have an association. Conclusions Maternal age of >35 years was and less walking hours/day were risk factors for spontaneous abortion Key Words: Cohort study; Risk factors; Spontaneous abortion DOI: 10.4038/jccpsl.v14i1.2943 Journal of the College of Community Physicians of Sri Lanka Vol.14(1) 2009 14-19